Kontribusi Kecerdasan Emosional terhadap Konflik Persahabatan pada Siswa SMP Negeri 1 Puding Besar, Bangka - Gian Nitary; Komarudin Komarudin (Islamic Psychology Study Program, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Characteristics of friendships are spending time together, interacting in diverse contexts, distancing others from the relationship, and offering emotional support to one another. But in friendship there are often conflicts. Conflict is a social phenomenon that can happen to anyone and anywhere. To resolve conflicts and disputes that occur with friends, teenagers are required to be able to control their emotions. Adolescents who are able to reduce and control emotions can be seen from the emotional intelligence of adolescents. Correct emotional balance, satisfaction classification, and mood regulation are all possible with emotional intelligence. This study uses a quantitative research methodology. In this study, the quantitative method was applied with a correlational approach. This research was conducted at SMP Negeri 1 Puding Besar with a population of 350 students, but the researchers took a sample of 50 students. The sampling technique is purposive sampling. Data retrieval by filling in the scale. Data analysis using Pearson Correlation Product Moment. The results of this study found that the contribution of emotional intelligence to friendly conflict obtained a significant level < 0.001 < 0.05 with a correlation coefficient of 0.494, meaning that emotional intelligence has a correlation with friendly conflict. The contribution of emotional intelligence to friendly conflict is a negative relationship, so it can be assumed that the higher the emotional intelligence, the lower the friendship conflict. Keywords: Emotional Intelligence, Friendship Conflict